EVALUATION OF SCIENCE LEARNING IN MIDDLE SCHOOLS: LITERATURE REVIEW - Fitriani, Riska; Saputra, Sendi Okta; Javed, Muhammad Ahmad (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
Learning evaluation is an activity to collect data and information about students' learning abilities, to assess the extent to which the learning program has been running, and also as a tool to determine whether educational goals and learning processes in developing knowledge have progressed as they are. Science assessments can be carried out in the cognitive, affective and psychomotor domains. This assessment provides space for students who tend to have non-academic weaknesses in science subject skills. This research was used to obtain information regarding the scope of evaluation of junior high school students' science learning. The review method was chosen to obtain research journals with the keywords scope of evaluation of junior high school science learning on reference sources Google Scholar, Elsevier, Science Direct, research gate, and publish or parish. 25 journals were reviewed based on author (year), research design, scope of evaluation, and findings. The results of the review show that the scope of learning evaluation can be carried out based on the context that wants to be assessed, such as the scope of the cognitive domain, affective domain and psychomotor domain. The scope of learning evaluation in the cognitive domain can be in the form of observation and understanding, the affective domain can be in the form of responses given by students as long as the teacher provides knowledge and the psychomotor domain in the form of skills assessment rubrics such as doing practical work after being given theory by the teacher.